2016
DOI: 10.1097/md.0000000000004706
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of early-onset atrial tachyarrhythmia after successful trans-catheter device closure of atrial septal defect

Abstract: Atrial tachyarrhythmia is a well-known long-term complication of atrial septal defect (ASD) in adults, even after successful trans-catheter closure. However, the risk factors for early-onset atrial tachyarrhythmia after trans-catheter closure remain unclear. This retrospective study enrolled adults with secundum ASD undergoing trans-catheter closure from January 2000 to March 2014. We analyzed the clinical characteristics of patients and assessed risk factors for new-onset atrial tachyarrhythmia defined as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Most newonset atrial tachyarrhythmias were documented within 6 months of closure. In the multivariate analysis, the risk for new-onset atrial tachyarrhythmia was significant in patients with AF/AFL during the closure, deficient posteroinferior rim, and age of closure over 48 years [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most newonset atrial tachyarrhythmias were documented within 6 months of closure. In the multivariate analysis, the risk for new-onset atrial tachyarrhythmia was significant in patients with AF/AFL during the closure, deficient posteroinferior rim, and age of closure over 48 years [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In literature, new onset arrhythmias after ASD device are significantly higher. Kyoung-Min Park et al, 24 have reported that 4.4% of the patients suffered with atrial tachyarrhythmia during the follow-up period of 11.4 months. It has been proposed that mechanical irritation caused by the devise could be associated with some arrhythmias (Spies et al 25 In present study, no case of arrhythmias in early, mid-term and long-term follow up was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the left atria (LA), remodeling is a not common to be accompaniment with LA enlargement in younger patients. Therefore, it is difficult to distinguish predictable factors for development of AF by LA size in ASD patients [6]. The factors associated with LA function and the changes in LA regarding myocardium remodeling after device closure should be defined.…”
Section: Open Accessmentioning
confidence: 99%